2023
DOI: 10.1002/oby.23815
|View full text |Cite
|
Sign up to set email alerts
|

High‐ and normal‐protein diets improve body composition and glucose control in adults with type 2 diabetes: a randomized trial

Abstract: Objective: Weight loss of ≥10% improves glucose control and may remit type 2 diabetes (T2D). High-protein (HP) diets are commonly used for weight loss, but whether protein sources, especially red meat, impact weight loss-induced T2D management is unknown. This trial compared an HP diet including beef and a normal-protein (NP) diet without red meat for weight loss, body composition changes, and glucose control in individuals with T2D.Methods: A total of 106 adults (80 female) with T2D consumed an HP (40% protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 36 publications
(45 reference statements)
0
2
0
Order By: Relevance
“…Some studies showed that increasing protein intake during energy-restricted diets has beneficial effects on body composition and the preservation of lean body mass (LBM) [ 13 , 14 , 17 , 22 , 23 , 24 ]. In contrast, we found that an increased protein intake of 1.5 g as compared to 1 g per kilogram of normalized weight neither affected weight loss nor LBM loss in the course of a 12-week multimodal treatment for morbid obesity with a formula-based diet of 800–1000 kcal per day.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies showed that increasing protein intake during energy-restricted diets has beneficial effects on body composition and the preservation of lean body mass (LBM) [ 13 , 14 , 17 , 22 , 23 , 24 ]. In contrast, we found that an increased protein intake of 1.5 g as compared to 1 g per kilogram of normalized weight neither affected weight loss nor LBM loss in the course of a 12-week multimodal treatment for morbid obesity with a formula-based diet of 800–1000 kcal per day.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies provided inconsistent results. Some found that increased protein intake during caloric restriction helps maintain LBM compared to normal protein intake [ 13 , 14 , 15 ], especially when combined with physical activity [ 16 , 17 ]. However, other studies have failed to show the positive impact of additional protein intake [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Other approaches, including time-restricted eating[ 11 ] and even high-protein diets[ 12 ], have successfully induced remission.…”
Section: Intensive Lifestyle Interventions For T2dm Remissionmentioning
confidence: 99%